Effect of Reverse Osmosis Wastewater on Seed Germination and seedling performance of four Different Crops - Sandamali, P.S.N.; Sivachandiran, S.; Ketheesan, B.; Asharp, G. (University of Jaffna, 2019)
Wastewater reclamation and its reuse for beneficial purposes is a common goal of many countries particularly in water stressed countries around the world. Cutting edge technologies such as reverse osmosis (RO), micro- and ultra-filtration are often used to purify underground water and wastewater generated from the industries. Wastewater is generated during the process of water purification with RO. However, the wastewater from these processes is usually laden with concentrated nutrients, salts, and other materials. Using RO rejection water as irrigation water for agriculture is a viable alternative. Hence, a study was conducted to assess the suitability of five different level of diluted RO wastewater along with control treatment (100% pure water) on seed germination and seedling performance of Amaranthus, cabbage, green gram and maize. This study was carried out in the laboratory with completely randomized design comprising three replicates. Purified water was used as control and used to prepare dilution levels of 20%, 40%, 60% and 80% along with RO wastewater. Seed germination percentage, germination time, shoot length, root length and fresh weight were recorded seven days after sowing and analyzed statistically. Significant differences (p<0.05) were found among treatments on germination percentage, germination time, root length, shoot length and fresh weight. Germination percentage decreased with the increasing percentage of RO rejected wastewater, while other parameters have shown slight fluctuations. Amaranthus and maize performed well with the combination of 40% wastewater and 60% purified water. Meanwhile, combination of 20% wastewater and 80% purified water showed positive effect on the germination of green gram (96.67%) and maize (100%). Furthermore, seven water quality parameters have shown a linear relationship with the fresh weight of sprouts. The results indicated that there is a possibility to use diluted reverse osmosis wastewater as source of irrigation water. Further, field studies needed to recommend the usage of RO rejected wastewater as part of irrigation water.
Keywords: Germination; Irrigation; Reverse osmosis; Wastewater